An UpdatedReview onBioinformatics and Pharmacogenomics in Drug Discovery and Development Process - Chakraborty, Arindam; Mukherjee, Payel; Chakraborty, Manas; kumar Singha, Dipak (Asian Journal of Pharmaceutical Research and Development, 2021)
Drug discovery and development is a time taking process, it has high risk also. Sometimes it get positive result, sometimes not. To discover, development and bring it into the market; pharmaceuticals companies invest millions of money. From drug discovery to bring it into the market these is a step by step procedure, it requires proper human resources, updated technological support and huge investment. A convenient surveillance is needed into the whole process from discovery to marketization that new entity. So these are the reasons for increasing cost in new drug development and research. But in recent time bioinformatics and pharmacogenomics made a huge impact on new drug development. Its helps in drug target identification, drug designing, clinical trial, not only bioinformatics and pharmacogenomics reduces the cost in healthcare management but also improves the selection of proper effective therapy and development of personalized medicines.